COMPUTER MODULE OF THE KDAM PROGRAM FOR DETERMINATION OF KINEMATIC AND DYNAMIC PARAMETERS OF THE CONNECTING ROD GROUP - SHCHERBAN, VOLODYMYR; KOLISKO, OKSANA; MELNIK, GENADIJ; KOLISKO, MARJANA; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The KDAM program is a structural element of a computer software complex for assessing the intensity of technological processes in the light and textile industry when determining the change in the relative tension of the thread in the filling zones of the technological equipment. Kinematic and dynamic analysis of flat mechanisms plays a significant role in the design of new mechanisms and modernization of existing ones. The results of these studies can be used to calculate the strength of individual links, their inertial characteristics, optimization of structural parameters of mechanisms, and minimization of consumed energy. The computer module of the KDAM program for determining the kinematic and dynamic parameters of the connecting rod-slider group of mechanisms of light industry machines allows you to determine the coordinates, velocity projections and accelerations of the center of mass of the connecting rod, the slider and the point of attachment of the links of the Asura groups on the connecting rod. During the dynamic analysis of the operation of the connecting rod-slider group, the projections of the full reaction in the joints between the crank and the connecting rod, between the connecting rod and the slider, and between the slider and the fixed guide are determined. Asura connecting rod-slider groups are widely used in light and textile industry machines. The output link of the connecting rod-slider group performs the function of the working body of the technological machine. The working body of the technological machine interacts with the threads. The trajectory of the movement of the working body affects the value of the angle of coverage of the guide surface by the thread. A change in the value of the coverage angle leads to a change in the tension of the threads. When the coverage angle increases to critical values, the thread may break and the technological equipment may stop. The tension of the thread increases when passing through the refueling zones of the thread feeding system on technological machines. The increase in tension is due to the crumpling of the thread in the area of contact with the guides. The maximum value of tension will be in front of the working area. A sharp increase in tension leads to a violation of the normal course of the technological process of thread processing. The development of new schemes of the thread feeding system requires an operational assessment of the value of the tension in front of the working zone. The objective function in the tasks of optimization of technological processes is the minimum necessary tension. The development of special computer programs for determining the tension in the working area makes it possible to determine the necessary technological parameters. The variable parameter in the objective function is the sum of the angles of coverage of the working bodies by the thread. The use of a computer program allows you to determine the tension and change in relative tension in the filling zones of technological machines, which allows you to optimize the shape of the thread supply line even at the stage of designing the technological process.